Complications in surgery and trauma - Cohn, Stephen M.; Dolich, Matthew O. (CRC Press, 2014)
This reference provides practical information on complications encountered during and after surgical procedures. It covers preoperative, intra-operative, and postoperative events such as organ transplant, amputations, nerve and fracture repair, and skin grafting. The author offers detailed guidance and techniques to recognize and control complications in the operating room, emergency ward, and intensive care unit. It icludes surgical sub-specialties such as critical care, endocrine, cardiothoracic, vascular, burns and wound healing, orthopedic, pediatric, and transplants. The new edition has been revised and reorganized to include nine new chapters and an update of the remaining chapters.